Mindfulness-based interventions to reduce anxiety among Chinese college students: A systematic review and meta-analysis - Li, Jun; Xu, Can; Wan, Keyan; Liu, Yihong; Liu, Liu (Frontiers in Psychology, 2023)
Mindfulness-based interventions are found to have a positive effect on an individual’s mental health. Using a meta-analysis method, this study examined the effects of mindfulness-based interventions on alleviating anxiety among Chinese college students. Using six international and two Chinese electronic databases, we comprehensively researched literature published between January 1, 2012 and December 31, 2021. The literature was then carefully selected and classified. The literature selection, data extraction, and quality assessment were all independently conducted by two members of the research team; any disagreements were resolved through consultation with a third researcher. A total of 11 original articles met all the eligibility criteria and were included in the meta-analysis. The meta-analysis revealed that mindfulness-based interventions have a positive effect on the remission of anxiety among Chinese college students. This confirms the need to generalize mindfulness-based interventions as a form of treatment and prevention for anxiety among Chinese college students.